Transforming Growth Factor β1 Induces the Expression of Collagen Type I by DNA Methylation in Cardiac Fibroblasts - Pan, Xiaodong; Chen, Zhongpu; Huang, Rong; Yao, Yuyu; Ma, Genshan (PLOS ONE, 2013)
Transforming growth factor-beta (TGF-β), a key mediator of cardiac fibroblast activation, has a major influence on collagen type I production. However, the epigenetic mechanisms by which TGF-β induces collagen type I alpha 1 (COL1A1) expression are not fully understood. This study was designed to examine whether or not DNA methylation is involved in TGF-β-induced COL1A1 expression in cardiac fibroblasts. Cells isolated from neonatal Sprague-Dawley rats were cultured and stimulated with TGF-β1. The mRNA levels of COL1A1 and DNA methyltransferases (DNMTs) were determined via quantitative polymerase chain reaction and the protein levels of collagen type I were determined via Western blot as well as enzyme-linked immunosorbent assay. The quantitative methylation of the COL1A1 promoter region was analyzed using the MassARRAY platform of Sequenom. Results showed that TGF-β1 upregulated the mRNA expression of COL1A1 and induced the synthesis of cell-associated and secreted collagen type I in cardiac fibroblasts. DNMT1 and DNMT3a expressions were significantly downregulated and the global DNMT activity was inhibited when treated with 10 ng/mL of TGF-β1 for 48 h. TGF-β1 treatment resulted in a significant reduction of the DNA methylation percentage across multiple CpG sites in the rat COL1A1 promoter. Thus, TGF-β1 can induce collagen type I expression through the inhibition of DNMT1 and DNMT3a expressions as well as global DNMT activity, thereby resulting in DNA demethylation of the COL1A1 promoter. These findings suggested that the DNMT-mediated DNA methylation is an important mechanism in regulating the TGF-β1-induced COL1A1 gene expression.